Empowering Spice-Based MSMEs through Branding, Packaging, and Digital Distribution: Community Service with KTH Majojo (ABDIMAS: Jurnal Pengabdian Masyarakat, 2025)
This participatory action research program aimed to empower the Majojo Forest Farmers Group (KTH Majojo) in Tidore Islands by strengthening branding, packaging, and digital distribution capacities. The intervention was implemented from June to August 2025 and involved 7 active members of KTH Majojo through 8 hands-on training and mentoring sessions, equipment provision, and distribution facilitation. Evaluation combined production and sales records with qualitative interviews and direct observation. After three months of intervention, measurable improvements were observed: average monthly sales increased by ≈50%, product packaging became more standardized, and the number of regular distribution outlets expanded from 0 to 3. Participants, particularly the group leader, reported higher confidence in using social media and marketplaces, and a digital product catalog was created for online channels. These results indicate that short-term, targeted capacity building combined with simple production tools can produce tangible gains in market access and product quality for spice-based MSMEs. The paper discusses implementation challenges, sustainability strategies, and recommendations for scaling the model to similar island communities.